Dielectric characterization of Plasmodium falciparum-infected red blood cells using microfluidic impedance cytometry. Issue 147 (17th October 2018) - Honrado, C.; Ciuffreda, L.; Spencer, D.; Ranford-Cartwright, L.; Morgan, H.
Abstract : Although malaria is the world's most life-threatening parasitic disease, there is no clear understanding of how certain biophysical properties of infected cells change during the malaria infection cycle. In this article, we use microfluidic impedance cytometry to measure the dielectric properties of Plasmodium falciparum -infected red blood cells ( i- RBCs) at specific time points during the infection cycle. Individual parasites were identified within i- RBCs using green fluorescent protein (GFP) emission. The dielectric properties of cell sub-populations were determined using the multi-shell model. Analysis showed that the membrane capacitance and cytoplasmic conductivity of i- RBCs increased along the infection time course, due to membrane alterations caused by parasite infection. The volume ratio occupied by the parasite was estimated to vary from less than 10% at earlier stages, to approximately 90% at later stages. This knowledge could be used to develop new label-free cell sorting techniques for sample pre-enrichment, improving diagnosis.